Case Report: Parental Loss and Childhood Grief During COVID-19 Pandemic - Santos, Susana; Sá, Teresa; Aguiar, Inês; Cardoso, Inês; Correia, Zulmira; Correia, Teresa (Frontiers in Psychiatry, 2021)
COVID19 pandemic is an unprecedent public health crisis, transforming many aspects of our daily life. Protection measures, such as social-distancing, nation-wide lockdowns, restrictions on hospital visits and funerals have a serious impact on how people mourn their loved ones. The grieving process during childhood and adolescence evolves along the developmental stages and is a dynamic, non-linear process that needs time. Parental death increases the risk for psychopathology in short and long-term. We present a case of an 11-years old girl referred to child psychiatry-liaison service by her neurologist due to peer relationship problems and sadness. Fifteen days before her first psychiatric consultation, her father suffered a myocardial infarction complicated with hypoxic ischemic encephalopathy, and he was hospitalized in intensive care unit. Positive coping mechanisms and adaptive emotional expression strategies were explored during her consultations. Her father died two weeks after emergency state and nation-wide lockdown was declared in Portugal, during first COVID19 outbreak. The family did not have the opportunity for a proper farewell, the funeral obeyed strict rules, and the patient and her family were at home, due to social-distancing and school closure policies. Consultations were maintained by telephone calls and, less frequently, by face-to-face appointments. Adaptive and helpful strategies to grieve were shared with the patient and her mother. Intervention with the mother alone was also helpful. Death circumstances related to COVID-19, confinement policies and social-economical stressors can intensify the grief experience, increasing the risk for complicated grief. Although psychiatric teleconsultation is essential during COVID19 pandemic, it poses various limitations. Nonverbal communication clues may not be totally apprehended, it may represent a problem in the therapeutic relationship and access to technology can be difficult for psychiatric patients and clinicians. COVID 19 pandemic policies should include mental health protection measures, which should facilitate adjusted grief responses for those who lose a loved one during this pandemic.